Corte Interamericana de Direitos Humanos e o Supremo Tribunal Federal: aplicação do princípio da complementaridade na responsabilidade internacional do Estado brasileiro - Portugal, Heloisa Helena de Almeida (2016)
Objective with this doctoral thesis demonstrate the viability of law-keeping Brazilian act of grace declared obstacle to compliance with the ruling to the detriment of Brazil for the Inter-American Court of Human Rights within the framework of the Case of Gomes Lund et al (Araguaia guerrilla movement) vs. . Brazil, 24.11.2010 sentence. It stands out, moreover, that a month before the court to rule in this sentence by a provision of Law 6,683 / 1979, the Supreme Court in ADPF 153 / DF judged incorporated this law by the Constitution of 1988. It appears that the Brazilian democratic formation compared in particular with the countries of South America, they showed different times, while in Brazil the transition took place through a negotiated political process and in the context of democratic transition, as a rule, in Latin America the amnesty occurs by imposition. Considering the inter-American system of human rights, the obligations and the international responsibility of State headquarters of violation of fundamental principles, it is concluded that the Supreme Court and the Inter-American Court of Human Rights consists of horizontal and complementary bodies. Having autonomy and government discretion to the decision of the supreme national court